Scenario Problem Based Learning on the Critical Thinking Ability of Vocational High School Students using the Piagetian Approach - Chendi Pirwanto Putra; Rahmania Sri Untari; Fitria Nur Hasanah; Elma Yunita (Graduate School of Universitas Negeri Malang, 2023)
Abstract: Students' low critical thinking skills in the learning process can affect the quality and results of student learning. This study aims to determine the influence of students' critical thinking skills by applying problem-based learning scenarios in primary computer and network subjects. This study used the Pre Experimental Design research with the One Group Pretest-Posttest Design. The subjects of this study were students of class X TKJ as the experimental group. The data collection technique used in this research is a critical thinking instrument. The data analysis used is a descriptive quantitative analysis using the Paired-Samples T-Test. The results showed that the problem-based learning scenario had no significant effect on the thinking skills of class X TKJ students.